Rare Benign Large Lymphoid Colonic Polyp - Yousef Alshamali; Ahmad Al Taleb; Talal Al-Taweel (Case Reports in Gastrointestinal Medicine)
Benign lymphoid polyps are uncommon lesions of the small bowel and the colon to a lesser degree that are mostly found in children. There are only few reported cases in adults in which the lesions were predominantly polypoid and described as lymphonodular hyperplasia. We present a case of a large benign lymphoid polyp in the transverse colon of a 64-year-old lady who was referred to our care for a history of alteration in her bowel habit and anemia. Colonoscopy showed a 3 cm (Paris 1p) friable polyp which was excised and retrieved. Histopathology examination confirmed its benign nature supported by immunohistochemical studies. Benign lymphoid polyp is a rare condition posing a diagnostic challenge as it can be misinterpreted as a malignant lesion.